Mapping the Sea Islands Culture in Paule Marshall's Praisesong For the Widow - Shamail, Ashma (Archīum Ateneo, 2024)
The Sea Islands off the coasts of Georgia and South Carolina function as a vital bridge between African Americans and their African ancestry, retaining a unique African culture that had been forgotten in the mainland communities. The Gullah/Geechee people, the inhabitants of the Sea Islands, are the most distinctive group of African Americans, who maintained a separate creole language and are unique from any other subset of African Americans. Paule Marshall’s vision of the Sea Islands in her 1983 novel Praisesong for the Widow illustrates the mythical landscape as a place for excavating and forging cultural as well as historical connections. The article focuses on the protagonist’s displaced historical memory, lost cultural connections, and self, which are awakened on the Sea Islands. Marshall links the Sea Islands and the African diaspora through the space of the Caribbean, emphasizing on discovering and recovering kinship ties. The protagonist’s understanding and awareness of a diasporic Gullah/Geechee identity comes to light when the Sea Island’s heritage wins over her oppressive American culture. The African diaspora is reunited in this novel through storytelling, dance, music, and rituals of reverence and remembrance, thereby enabling the protagonist to acknowledge and identify her Gullah roots and culture. As retrieval of real and imagined cultural inheritances is crucial to the construction and process of creolized identities, Marshall posits the Sea Islands as central and a site of cultural expression in the novel. Marshall’s depiction of the Sea Island’s role in Praisesong as a unique southern landscape serves as a healing ground for physical and cultural loss.